Etiopathogenic diagnostic and therapeutic aspects of periimplantitis - Ferati, Kenan (PONS - medicinski časopis, 2015)
Abstract   The term implantation involves the installation of a dedicated specially designed allogeneic material in live tissu.Oralna implantology as an integral part of dentistry, aims to make up for lost teeth, and at the same time to improve the function of chewing, speech and aesthetics. In a certain number of patient with implant there can be certain complications, even complete implant failure at the level of installation. Such complications can arise immediately after implant placement or later, when the implant osseointegration is achieved and put into operation, ie in the phase of prosthetic reconstruction, or after setting superstructure.It can be said that the success of the osseointegration of implants is depending on: the biological nature of bone tissue, physical characteristics, construction, building and forces to which it is exposed after its making. After this process it comes clearly that balance is necessary between the force to which an implant and superstructure is subjected on the one hand and the resistance structure, which ensures its support during oral masticatory function, on the other hand.   Keywords: Peri-Implantitis, Dental Implants, Oral Hygiene, Periodontal pockets